Twenty-five years of co-management of caribou in northern Québec - Dion, René (Rangifer, 2003)
The Hunting Fishing and Trapping Co-ordinating Committee (HFTCC), created at the signature of the James Bay and Northern Quebec Agreement has been meeting regularly since 1977. Early in the process, it became clear that the perception of the role and powers of the Committee were not commonly shared by the native and non-native members of the Committee. Nevertheless, the Committee has been used primarily as a consultative body for wildlife related issues. Of all the files on which the Committee worked, Caribou management, (including the development of outfitting and commercial hunting for this species) has been among one of the most discussed subjects during the meetings. An analysis of important decisions taken and of the process that led to them reveal that very rarely was the Committee able to formulate unanimous resolutions to the Governments concerning caribou management. In fact, only a few unanimous resolutions could be traced and many were ignored. This took place during a period of abundance and growth of the caribou herds. As a result, the Committee has gone through the cycle of growth of the George River Herd without a management plan, without a long term outfitting management plan and for the last 8 years, without a population estimate of the herds. This situation did not prevent the Committee from allocating quotas for a commercial hunt, open a winter sport hunt and to give permanent status to outfitting camps that were once established as mobile camps. It was hoped then that increased harvest would help maintain the population at carrying capacity. This short-term reaction however, never evolved into a more elaborate plan. Of course this must be looked at in the context of the HFTCC having a lot more to worry about than the Caribou. Although all members know of the population cycles of caribou, the decision process that must be triggered, should a crisis occur is not in place. This presently results into a polarization of concerned users (fall outfitters vs. winter outfitters, subsistence and sport hunters vs. commercial hunt, Outfitters Associations vs. HFTCC and eventually George River Herd users vs. Leaf River Herd users. The HFTCC may have to make difficult decisions during the coming years but did not gain much constructive experience through its first 25 years of existence. It is unfortunate that the authority of the Committee is binding the governments only in times of crisis when an upper limit of kill needs to be established. Because of the unpredictability of caribou herd numbers, the upper limit of kill should be established on a yearly basis. This would insure that the committee is fed information continuously in order to make informed decisions and would also re-establish the authority of the HFTCC over this resource.